Analytical Methods for Determining the Peroxide Value of Hemp Seed (Cannabis Sativa L.) Oil - Yildiz, Yusuf; Duchaine, Yvan; Ergin, Zehra N. (European Journal of Applied Sciences, 2025)
The peroxide Value is the number that expresses, in milli equivalents of active oxygen, the quantity of peroxide contained in 1000 g of the substance. Hemp seed oil containing essential omega fatty acids and proteins. This organic hemp seed oil has a pleasant nutty smell, deep green hue, and absorbs well into the skin. Hemp-seed oil has several positive effects on skin problems such as dryness and those related to the aging process. Hemp seed oil sample were peroxide value (POV) assayed using a standard starch solution, American Oil Chemist’s Society (AOCS) Method Cd 8-53, and used as a verified reference method for peroxide determination. Peroxide values (POV) is a standard test in the food and cosmetic industry to ensure product quality and self-life. In this study, peroxide value in Hemp Seed (Cannabis Sativa L.) oil has been determined by iodometric titration method using acetic acid-chloroform reagent. The average result is less than 4.0 meq O2 / Kg. Relative repeatability Standard Deviation %RSD is 2.64 %. The average result meets the specification.